Learning amid crisis: the impact of the ongoing conflict on the academic and personal lives of university students in Lebanon - Kharroubi, Samer A. (Frontiers in Education, 2025)
As the ongoing conflict in Lebanon escalates, it has deeply impacted various aspects of daily life, with significant consequences on students’ academic and personal experiences. This research utilized real-time survey data from students at the American University of Beirut (AUB) to evaluate how the crisis affects their academic progress, personal lives, and the challenges associated with transitioning to online and hybrid learning models. An online survey (n = 3,430) was administered between October 5 and October 12, 2024, using Google Forms. The survey comprised four sections: sociodemographic characteristics, personal circumstances, academic impact, and personal well-being. The findings reveal widespread student displacement, disrupting both education and overall well-being. This study offers a critical evidence base, emphasizing students’ urgent needs and providing the foundation for future investigations and the development of efficient crisis-assistance programs within higher education.